2015
DOI: 10.3390/nano5020565
|View full text |Cite
|
Sign up to set email alerts
|

Metal Organic Framework Micro/Nanopillars of Cu(BTC)·3H2O and Zn(ADC)·DMSO

Abstract: In this work, we report the optical and thermal properties of Cu(BTC)·3H2O (BTC = 1,3,5-benzenetricarboxylic acid) and Zn(ADC)·DMSO (ADC = 9,10-anthracenedicarboxylic acid, DMSO = dimethyl sulfoxide) metal-organic frameworks (MOFs) micro/nanopillars. The morphologies of MOFs on surfaces are most in the form of micro/nanopillars that were vertically oriented on the surface. The size and morphology of the pillars depend on the evaporation time, concentration, solvent, substrate, and starting volume of solutions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Self-assembly processes driven by diverse interactions can generate a myriad of nanostructures by using nanocrystals as building blocks. Shape control of these structures can be achieved by tuning some of the synthesis parameters such as temperature, type of ligands, and interaction of the ligands with the precursors and/or the nanoparticles [ 4 , 5 , 6 ]. This means that the thermodynamics and kinetics of nucleation and growth can also be controlled [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly processes driven by diverse interactions can generate a myriad of nanostructures by using nanocrystals as building blocks. Shape control of these structures can be achieved by tuning some of the synthesis parameters such as temperature, type of ligands, and interaction of the ligands with the precursors and/or the nanoparticles [ 4 , 5 , 6 ]. This means that the thermodynamics and kinetics of nucleation and growth can also be controlled [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phase structure of the Cu‐BTCs synthesized in SS1 and SS2 was shown in figure 4. Comparing the results with data from the literature (table 2), [ 20,41 ] it can be concluded that the Cu‐BTC synthesized in SS1 is a mixture of 1D structure catena‐triaqua μ ‐ [1,3,5‐benzenetricarboxylato]‐copper(II) corresponding to the formula [Cu(BTC)(H 2 O) 3 ] n and micropillar structure Cu(BTC).3H 2 O. [ 20,37,41 ] This will be confỉmed by the SEM result below.…”
Section: Resultsmentioning
confidence: 56%
“…The formation of Cu(Hbtc)(H 2 O) 3 needles might be promoted by two factors: 1) pore size of the foam support material, and 2) application of an alumina coating. Pure Cu(Hbtc)(H 2 O) 3 is usually formed in aqueous solutions with low concentrations of copper and trimesate ions [42,43]. This strong promotion effect of an alumina coating on the foam is most likely explained by altering the hydrophilic properties of the strut surface by increasing the -OH coverage, and it might lead to the formation of an increased number of seeds for the Cu(Hbtc)(H 2 O) 3 3 side product.…”
Section: Discussionmentioning
confidence: 99%